Robust Icephobic Performance of Flexible Needles. Issue 2 (28th November 2018) - Liu, Xuejuan; Zhao, Hongbin; Li, Peiliu; Pang, Yan; Fan, Yuzun; Zhang, Bo; Wang, Lei; Zheng, Yongmei; Wang, Zuankai
Abstract: Superhydrophobic micro‐/nanopatterned structures exhibit robust water/ice repellence in harsh environments, which is significant for theoretical study and industrial applications such as cooling in nuclear power, heat transfer, and self‐cleaning for aircraft. However, the reported studies regarding icephobic functional surfaces based on rigid materials have indicated potential dangers in applications, e. g., the roughness topographies are easily ruined in the icing process, which limits further application and study. In this study, polydimethylsiloxane‐based flexible microneedles (FNs) with ZnO nanorods are designed and fabricated and further characterized with robust icephobicity at a temperature of 0 °C. In this system, the flexible microneedles could bend to match the deformation caused by icing from condensed droplets, resulting in protecting the nanorods on its surface, which is significantly promising for durable icephobicity in harsh environments. Abstract : Robust Icephobicity : A superhydrophobic, self‐cleaning surface made of flexible needles has been designed that is anti‐icing at low temperatures. The flexible microneedles can bend to match the deformation caused by icing, which protects the nanorods and ensures stable performance.